This I Believe - Richie, David S. (Tufts Archival Research Center, 2006)
David Richie mentions a social experiment he tried in which he behaved selfishly one week and selflessly the following, what he discovered is that he felt better when acting selflessly and he believes now that good deeds can only be accomplished through good means.